A Needs Analysis of Nursing Students’ English Proficiency, Learning Goals, and Content Preferences in English for Nursing Courses - May Lorenna (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Needs analysis plays a crucial role in designing effective English for Specific Purposes (ESP) courses, particularly in nursing education, where language skills are essential for professional communication. This study aimed to analyze nursing students’ English proficiency, learning goals, and content preferences to provide insights for the development of English for Nursing courses. Employing a descriptive quantitative design, data were collected through a questionnaire administered to 33 nursing students of the sixth semester at Poltekkes Kemenkes Semarang. The findings revealed that most students were interested in learning English and perceived it as important for their future careers. In terms of English proficiency, reading was identified as the strongest skill, while speaking was the weakest. The primary goals for learning English were to support future careers, communicate with foreigners, and understand academic texts and journal articles. Regarding content preferences, students considered nursing-related topics such as patient admission, patient education, standard operating procedures, checking vital signs, and reporting health problems as highly important. These findings suggest that English for Nursing courses should place greater emphasis on developing speaking skills and integrating authentic nursing-related materials that reflect real clinical situations. The study highlights the importance of conducting needs analysis to ensure that English instruction is relevant to students’ academic and professional needs.